Preparation method of microporous copper foil

By using electrochemical etching and passivation methods, combined with corrosion inhibitors, complexing agents, and surfactants, the pore size and morphology of microporous copper foil are controlled, solving the problem of uneven pore size in existing technologies and improving the performance of lithium-ion batteries.

CN121006593APending Publication Date: 2025-11-25JIUJIANG AMBER NEW MATERIALS CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511127686.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-12
Publication Date
2025-11-25

AI Technical Summary

Technical Problem

Existing technologies struggle to effectively control the pore size and morphology of microporous copper foil, resulting in unpenetrated blind holes and micropores of varying shapes, which negatively impact the performance of lithium-ion batteries.

Method used

A method combining electrochemical etching with corrosion inhibitors, complexing agents, and surfactants is used to form copper foil in an etching solution through a cathode plate at specific locations, followed by passivation treatment in an anti-oxidation solution to control the formation and size of micropores.

Benefits of technology

The uniform distribution and control of the pore size of the microporous copper foil were achieved, which improved the performance of lithium-ion batteries and met the requirements for lightweighting and fast charging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005545734680000011
    Figure HDA0005545734680000011
  • Figure HDA0005545734680000012
    Figure HDA0005545734680000012
Patent Text Reader

Abstract

The invention provides a microporous copper foil preparation method, which comprises: mixing an oxidizing agent, a corrosion inhibitor, a complexing agent, a surfactant and water, and adjusting the pH value to obtain a corrosive liquid; performing electrochemical etching in the corrosive liquid by taking the electrolytic copper foil as an anode and a cathode plate at a specific point location as a cathode to form a copper foil; and cleaning the etched copper foil, and passivating the cleaned copper foil in an anti-oxidation solution to obtain the microporous copper foil. The method provided by the invention comprises the following steps: taking a copper foil as a corrosive anode, forming an electrolytic tank with a cathode plate at a specific point location and a corrosive liquid, carrying out site oxidation on the surface of the copper foil through an oxidant, and carrying out acid corrosion on the site to form a blind hole; in order to ensure that the corrosion degree of the copper foil is consistent, blind holes are formed, a corrosion inhibitor, a surfactant and a complexing agent are combined, and the corrosion rate of the copper foil is reduced; the method can effectively control the formation of copper foil micropores and the size of the pore diameter.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of metal surface treatment technology, and particularly relates to a method for preparing microporous copper foil. Background Technology

[0002] Microporous copper foil represents a revolutionary direction for current collector materials in lithium-ion batteries. By constructing controllable micron-scale pore structures (pore size 1–20 μm, porosity 10–40%) on or within the copper foil surface, it overcomes the functional limitations of traditional copper foil, becoming a key material for the development of high-energy-density, high-power, and flexible batteries. With the continuous upgrading of battery performance requirements from new energy vehicles, portable electronic devices, and flexible electronic products, traditional copper foil, due to its high weight ratio, single ion transport path, and insufficient interfacial bonding, struggles to meet the demands for lightweight, fast-charging, and flexible battery designs. Microporous copper foil, through its integrated structure-function design combined with advanced processes such as precision etching and electrochemical deposition, achieves a leapfrog improvement in material performance. Its technological advantages have profound significance for the evolution of lithium battery technology and industrial upgrading.

[0003] The key to preparing microporous copper foil lies in controlling the size and morphology of its micropores. Conventional electrochemical etching or microporous copper foil formed by adjusting the roughness of the cathode is prone to producing blind holes and micropores of different shapes, and even large holes formed by multiple holes connected together. This can easily lead to slurry leakage in the downstream slurry coating process. Summary of the Invention

[0004] In view of this, the purpose of the present invention is to provide a method for preparing microporous copper foil, which can effectively control the formation and size of the micropores in the copper foil.

[0005] This invention provides a method for preparing microporous copper foil, comprising the following steps:

[0006] An oxidizing agent, corrosion inhibitor, complexing agent, surfactant, and water are mixed, and the pH is adjusted to obtain a corrosion solution.

[0007] Electrochemical etching is performed in an etching solution using electrolytic copper foil as the anode and a cathode plate at a specific location as the cathode to form copper foil.

[0008] The etched copper foil is cleaned and then passivated in an anti-oxidation solution to obtain microporous copper foil.

[0009] Preferably, the oxidant is selected from one or more of hydrogen peroxide, potassium permanganate, and hypochlorous acid;

[0010] The corrosion inhibitor is selected from benzotriazole and / or 2-mercaptobenzimidazole;

[0011] The complexing agent is selected from one or more of citric acid, tartaric acid and succinic acid;

[0012] The surfactant is selected from sodium dodecyl sulfate and / or betaine.

[0013] Preferably, the concentration of the oxidant is 10–100 g / L; the concentration of the corrosion inhibitor is 1–20 g / L.

[0014] The concentration of the complexing agent is 5–50 g / L; the concentration of the surfactant is 0.2–2 g / L.

[0015] Preferably, dilute sulfuric acid is used to adjust the pH value to 2-3.

[0016] Preferably, the corrosive solution comprises 50 g / L hydrogen peroxide, 10 g / L benzotriazole, 30 g / L citric acid, and 0.5 g / L sodium dodecyl sulfate, all at a mass fraction of 30%.

[0017] Alternatively, the corrosive solution may contain 10 g / L potassium permanganate, 6 g / L 2-mercaptobenzimidazole, 18 g / L citric acid, 10 g / L tartaric acid, and 0.5 g / L sodium dodecyl sulfate.

[0018] Alternatively, the corrosive solution may comprise 50 g / L hydrogen peroxide, 10 g / L benzotriazole, 10 g / L citric acid, 5 g / L succinic acid, and 0.2 g / L betaine, all at a mass fraction of 30%.

[0019] Alternatively, the corrosive solution may comprise 30 g / L hydrogen peroxide, 10 g / L benzotriazole, 5 g / L 2-mercaptobenzimidazole, 10 g / L citric acid, 5 g / L tartaric acid, and 0.2 g / L betaine, all at a mass fraction of 30%.

[0020] Preferably, the cathode plate is a titanium plate with multiple micro-protrusions evenly distributed on its surface.

[0021] Preferably, the distance between adjacent micro-protrusions is 2 to 10 mm.

[0022] Preferably, the etching process uses a current density of 20–50 mA / cm². 2 ;

[0023] The etching time is 10 to 30 seconds.

[0024] Preferably, the main component of the anti-oxidation solution is a chromium passivation solution.

[0025] Preferably, acid etching is performed before cleaning; the acid etching is performed by soaking in dilute hydrochloric acid with a mass fraction of 3-6% for 4-6 seconds to form a microporous structure with a pore size of 5-20 μm.

[0026] This invention provides a method for preparing microporous copper foil, comprising the following steps: mixing an oxidant, a corrosion inhibitor, a complexing agent, a surfactant, and water; adjusting the pH value to obtain an etching solution; using an electrolytic copper foil as the anode and a cathode plate at a specific location as the cathode, performing electrochemical etching in the etching solution to form a copper foil; cleaning the etched copper foil and then passivating it in an anti-oxidation solution to obtain microporous copper foil. The method provided by this invention uses copper foil as the corrosive anode, forming an electrolytic cell with a cathode plate at a specific location and the etching solution. The oxidant performs site oxidation on the copper foil surface, forming blind holes through acid etching. To ensure consistent corrosion of the copper foil and the formation of blind holes, a corrosion inhibitor, surfactant, and complexing agent are combined to reduce the corrosion rate of the copper foil. This method can effectively control the formation and size of micropores in the copper foil. Attached Figure Description

[0027] Figure 1 This is a SEM image of the micropores in the copper foil prepared in Example 1 of the present invention after etching.

[0028] Figure 2 This is a detection diagram of the aperture after etching the copper foil in Embodiment 1 of the present invention. Detailed Implementation

[0029] This invention provides a method for preparing microporous copper foil, comprising the following steps:

[0030] An oxidizing agent, corrosion inhibitor, complexing agent, surfactant, and water are mixed, and the pH is adjusted to obtain a corrosion solution.

[0031] Electrochemical etching is performed in an etching solution using electrolytic copper foil as the anode and a cathode plate at a specific location as the cathode to form copper foil.

[0032] The etched copper foil is cleaned and then passivated in an anti-oxidation solution to obtain microporous copper foil.

[0033] The method provided by this invention uses copper foil as a corrosive anode to form an electrolytic cell with a cathode plate and a corrosive solution at specific locations. The copper foil surface is oxidized at specific sites by an oxidant, and blind holes are formed by acid corrosion at these sites. To ensure that the copper foil is corroded to a uniform degree and forms blind holes, corrosion inhibitors, surfactants and complexing agents are combined to reduce the corrosion rate of the copper foil. This method can effectively control the formation and size of micropores in the copper foil.

[0034] This invention involves mixing an oxidant, a corrosion inhibitor, a complexing agent, a surfactant, and water, and adjusting the pH to obtain a corrosive solution. In this invention, the oxidant is selected from one or more of hydrogen peroxide, potassium permanganate, and hypochlorous acid; the corrosion inhibitor is selected from benzo[a]azole and / or 2-mercaptobenzimidazole; the complexing agent is selected from one or more of citric acid, tartaric acid, and succinic acid; and the surfactant is selected from sodium dodecyl sulfate and / or betaine.

[0035] The corrosion inhibitor described in this invention mainly functions to reduce the impact of the tip current on the etching of the copper foil. The surfactant mainly enhances the adsorption of the corrosion inhibitor and complexing agent on the copper foil surface, while the complexing agent mainly promotes the etching of the copper foil.

[0036] In this invention, the concentration of the oxidant is 10–100 g / L, specifically 10 g / L, 20 g / L, 30 g / L, 40 g / L, 50 g / L, 60 g / L, 70 g / L, 80 g / L, 90 g / L, or 100 g / L; the concentration of the corrosion inhibitor is 1–20 g / L, specifically 2 g / L, 4 g / L, 6 g / L, 8 g / L, 10 g / L, 12 g / L, 14 g / L, 16 g / L, 18 g / L, or 20 g / L; The concentration of the complexing agent is 5–50 g / L, specifically 5 g / L, 10 g / L, 15 g / L, 20 g / L, 25 g / L, 30 g / L, 35 g / L, 40 g / L, 45 g / L, or 50 g / L; the concentration of the surfactant is 0.2–2 g / L, specifically 0.2 g / L, 0.4 g / L, 0.6 g / L, 0.8 g / L, 1.0 g / L, 1.2 g / L, 1.4 g / L, 1.6 g / L, 1.8 g / L, or 2.0 g / L.

[0037] The present invention preferably uses dilute sulfuric acid to adjust the pH to 2-3.

[0038] In this invention, the corrosive solution comprises 50 g / L hydrogen peroxide, 10 g / L benzotriazole, 30 g / L citric acid, and 0.5 g / L sodium dodecyl sulfate, all at a mass fraction of 30%.

[0039] Alternatively, the corrosive solution may contain 10 g / L potassium permanganate, 6 g / L 2-mercaptobenzimidazole, 18 g / L citric acid, 10 g / L tartaric acid, and 0.5 g / L sodium dodecyl sulfate.

[0040] Alternatively, the corrosive solution may comprise 50 g / L hydrogen peroxide, 10 g / L benzotriazole, 10 g / L citric acid, 5 g / L succinic acid, and 0.2 g / L betaine, all at a mass fraction of 30%.

[0041] Alternatively, the corrosive solution may comprise 30 g / L hydrogen peroxide, 10 g / L benzotriazole, 5 g / L 2-mercaptobenzimidazole, 10 g / L citric acid, 5 g / L tartaric acid, and 0.2 g / L betaine, all at a mass fraction of 30%.

[0042] This invention uses electrolytic copper foil as the anode and a cathode plate at a specific location as the cathode to perform electrochemical etching in an etching solution to form copper foil.

[0043] In this invention, the etching current density is 20–50 mA / cm². 2Specifically, it can be 20mA / cm 2 25mA / cm 2 30mA / cm 2 35mA / cm 2 40mA / cm 2 45mA / cm 2 Or 50mA / cm 2 The etching time is 10–30 seconds, specifically 10, 12, 14, 16, 18, 20, 22, 24, 26, 28, or 30 seconds. Continuous agitation is required during the etching process to eliminate concentration polarization.

[0044] In this invention, the cathode plate at a specific location is a titanium plate with uniformly distributed micro-bumps on its surface, spaced 2–10 mm apart; specifically, the micro-bumps can be 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, or 10 mm. During the copper foil etching process, the micro-bumps on the cathode plate easily cause the copper foil to form micropores, the size of which is related to the size and spacing of the micro-bumps. The cathode plate at the specific location was purchased from Standard.

[0045] This invention involves cleaning the etched copper foil and then passivating it in an anti-oxidation solution to obtain a microporous copper foil. After etching, the copper foil has many surface active sites, so it is necessary to promptly wash off the residual etching solution with clean water before placing it in an anti-oxidation solution for passivation.

[0046] This invention involves acid etching before cleaning; the acid etching is performed by immersing the sample in 3-6% hydrochloric acid for 4-6 seconds to form a microporous structure with a pore size of 5-20 μm. In a specific embodiment, immersion in 5% hydrochloric acid for 5 seconds selectively etches the oxidation sites, generating micropores.

[0047] In this invention, the main component of the anti-oxidation solution is a chromium passivation solution. This invention does not impose any special limitations on the chromium passivation solution; any chromium passivation solution well-known to those skilled in the art can be used. In a specific embodiment, the chromium passivation solution contains CrO3 and H2SO4, with a mass concentration ratio of CrO3 to H2SO4 of 5:1. Preferably, the solution is placed in the anti-oxidation solution at room temperature for 8–12 seconds to form a passivation film.

[0048] After passivation, the copper foil is removed and dried, preferably using hot air at 70–90°C for 4–6 minutes, to obtain a microporous copper foil with no surface oxidation and uniform blind hole distribution. Specifically, it is dried with hot air at 80°C for 5 minutes.

[0049] To further illustrate the present invention, the following detailed description of a method for preparing a microporous copper foil provided by the present invention is provided in conjunction with embodiments, but these should not be construed as limiting the scope of protection of the present invention.

[0050] Comparative Example 1:

[0051] Oxidizing agent: hydrogen peroxide (H2O2, 30% concentration), 50 g / L; corrosion inhibitor: benzotriazole (BTA), 10 g / L; surfactant: sodium dodecyl sulfate (SDS), 0.5 g / L. Dissolve the above components sequentially in water, stirring until completely mixed. Adjust the pH of the solution to 2-3 with dilute sulfuric acid to obtain a homogeneous and transparent etching solution. Pour the prepared etching solution into the electrolytic cell, ensuring the liquid level completely covers the copper foil. Use a 6 μm thick electrolytic copper foil (10 cm × 10 cm) as the anode (surface roughness ≤ 1.5 μm); use a titanium plate with uniformly distributed micro-bumps on its surface as the cathode (spacing: 3 mm). Connect a DC power supply, controlling the current density at 35 mA / cm², and the etching time at 20 s. Maintain the solution temperature at 25 ± 2℃ during etching and continuously circulate and stir to eliminate concentration polarization. After etching, uniformly distributed oxide sites are formed on the surface of the copper foil. Immersion in dilute hydrochloric acid (5% concentration) for 5 seconds selectively corrodes these oxide sites, generating a microporous structure with a pore size of 100–200 μm. The etched copper foil is immediately rinsed three times with deionized water to remove residual etching solution. It is then immersed in a chromate passivation solution (containing 5 g / L CrO3 and 1 g / L H2SO4) at room temperature for 10 seconds to form a passivation film. After removal, it is blown dry and then dried with hot air at 80°C for 5 minutes, resulting in a microporous copper foil with no oxide surface and uniformly distributed blind holes.

[0052] Comparative Example 2:

[0053] Oxidizing agent: hydrogen peroxide (H2O2, 30% concentration), 50 g / L; Complexing agent: citric acid (C6H8O7), 30 g / L; Surfactant: sodium dodecyl sulfate (SDS), 0.5 g / L. Dissolve the above components sequentially in water, stirring until completely mixed. Adjust the pH of the solution to 2-3 with dilute sulfuric acid to obtain a homogeneous and transparent etching solution. Pour the prepared etching solution into the electrolytic cell, ensuring the liquid level completely covers the copper foil. Use a 6 μm thick electrolytic copper foil as the anode (10 cm × 10 cm), with a surface roughness ≤1.5 μm; use a titanium plate with uniformly distributed micro-bumps on its surface as the cathode (spacing: 3 mm). Connect a DC power supply and control the current density to 35 mA / cm². 2 The etching time was 20 seconds. During etching, the solution temperature was maintained at 25±2℃, and continuous circulation and stirring were performed to eliminate concentration polarization. The copper foil surface was uniformly etched, turning the entire surface black without obvious perforations, and the copper foil thickness was approximately 5 μm. After immersion in dilute hydrochloric acid (5% concentration) for 5 seconds, the etched copper foil was immediately rinsed three times with deionized water to remove residual etching solution. It was then immersed in a chromate passivation solution (containing 5 g / L CrO3 and 1 g / L H2SO4) at room temperature for 10 seconds to form a passivation film. After removal, it was blown dry and then dried with hot air at 80℃ for 5 minutes to obtain a microporous copper foil with uniformly distributed blind holes on the surface.

[0054] Example 1:

[0055] Oxidizing agent: hydrogen peroxide (H2O2, 30% wt concentration), 50 g / L; corrosion inhibitor: benzotriazole (BTA), 10 g / L; complexing agent: citric acid (C6H8O7), 30 g / L; surfactant: sodium dodecyl sulfate (SDS), 0.5 g / L. Dissolve the above components sequentially in water, stirring until completely mixed. Adjust the pH of the solution to 2-3 with dilute sulfuric acid to obtain a homogeneous and transparent etching solution. Pour the prepared etching solution into an electrolytic cell, ensuring the liquid level completely covers the copper foil. Use a 6 μm thick electrolytic copper foil (10 cm × 10 cm) as the anode (surface roughness ≤ 1.5 μm); use a titanium plate with uniformly distributed micro-bumps on its surface as the cathode (spacing: 3 mm). Connect a DC power supply, controlling the current density at 35 mA / cm², and the etching time at 20 s. Maintain the solution temperature at 25 ± 2℃ during etching and continuously circulate and stir to eliminate concentration polarization. After etching, uniformly distributed oxide sites are formed on the surface of the copper foil. Immersion in dilute hydrochloric acid (5% concentration) for 5 seconds selectively etches these oxide sites, generating a microporous structure with a pore size of 5–20 μm. The etched copper foil is immediately rinsed three times with deionized water to remove residual etching solution. It is then immersed in a chromate passivation solution (containing 5 g / L CrO3 and 1 g / L H2SO4) at room temperature for 10 seconds to form a passivation film. After removal, it is blown dry and then dried with hot air at 80℃ for 5 minutes, resulting in a microporous copper foil with no oxide surface and uniformly distributed blind holes. The pore size of the foil surface is characterized using a micropore detector, and the data are shown in Tables 1 and 2. The instrument detected a foil area of ​​6645522.64 μm. 2 There are a total of 179 micropore sites, with a total micropore area of ​​7247.17 μm. 2 The total area accounts for 0.11%, with an average minimum diameter of 4.75 μm and an average maximum diameter of 5.99 μm.

[0056] Table 1. Aperture data for some test points

[0057] No. Minimum diameter / μm <![CDATA[Area / μm 2 > Circumference / μm Maximum diameter / μm 1 2.07 13.89 11.80 4.62 2 5.55 38.46 21.42 7.31 3 8.77 83.33 31.40 10.39 4 7.24 58.76 27.02 8.89 5 0.00 1.07 0.00 0.00 6 4.39 34.18 19.11 7.45 7 7.24 56.62 27.02 8.83 8 9.30 97.21 33.83 11.18

[0058] Table 2 Summary of Aperture Data

[0059] Minimum diameter / μm <![CDATA[Area / μm 2 > Circumference / μm Maximum diameter / μm average 4.75 40.49 17.78 5.99 Standard deviation 3.66 36.76 13.10 4.28 maximum 12.40 146.35 46.13 14.06 Minimum 0.00 1.07 0.00 0.00 total 851.07 7247.17 3182.15 1073.06

[0060] Example 2:

[0061] Oxidizing agent: potassium permanganate (KMnO4), 10 g / L; corrosion inhibitor: 2-mercaptobenzimidazole (C7H6N2S), 6 g / L; complexing agent: citric acid (C6H8O7), 18 g / L, tartaric acid (TA), 10 g / L; surfactant: sodium dodecyl sulfate (SDS), 0.5 g / L. Dissolve the above components sequentially in water, stirring until completely mixed. Adjust the pH of the solution to 2-3 with dilute sulfuric acid to obtain a homogeneous and transparent etching solution. Pour the prepared etching solution into an electrolytic cell, ensuring the liquid level completely covers the copper foil. Use a 6 μm thick electrolytic copper foil (10 cm × 10 cm) as the anode (surface roughness ≤ 1.5 μm); use a titanium plate with uniformly distributed micro-bumps on its surface as the cathode (spacing: 3 mm). Connect a DC power supply, control the current density at 25 mA / cm², and the etching time at 20 s. During etching, the solution temperature was maintained at 25±2℃, and continuous circulation and stirring were performed to eliminate concentration polarization. After etching, uniformly distributed oxide sites were formed on the surface of the copper foil. After immersion in dilute hydrochloric acid (5% concentration) for 5 seconds, the oxide sites were selectively etched, generating a microporous structure with a pore size of 5-20 μm. The etched copper foil was immediately rinsed three times with deionized water to remove residual etching solution. It was then immersed in a chromate passivation solution (containing 5 g / L CrO3 and 1 g / L H2SO4) at room temperature for 10 seconds to form a passivation film. After removal, it was blown dry and dried with hot air at 80℃ for 5 minutes to obtain a microporous copper foil with no oxidation on the surface and a uniform distribution of blind holes.

[0062] Example 3:

[0063] Oxidizing agent: hydrogen peroxide (H2O2, 30% concentration), 50 g / L; Corrosion inhibitor: benzotriazole (BTA), 10 g / L; Complexing agent: citric acid (C6H8O7), 10 g / L, succinic acid (C4H6O4), 5 g / L; Surfactant: betaine (C5H 11NO2), dosage 0.2 g / L. Dissolve the above components sequentially in water, stirring until completely mixed. Adjust the pH of the solution to 2-3 with dilute sulfuric acid to obtain a homogeneous and transparent etching solution. Pour the prepared etching solution into the electrolytic cell, ensuring the liquid level completely covers the copper foil. Use a 6 μm thick electrolytic copper foil (10 cm × 10 cm) as the anode (surface roughness ≤ 1.5 μm); use a titanium plate with uniformly distributed micro-bumps on its surface as the cathode (spacing: 3 mm). Connect a DC power supply, controlling the current density at 45 mA / cm², and the etching time at 10 s. Maintain the solution temperature at 25 ± 2℃ during etching and continuously circulate and stir to eliminate concentration polarization. After etching, uniformly distributed oxide sites are formed on the copper foil surface. Immerse in dilute hydrochloric acid (5% concentration) for 5 s; the oxide sites are selectively etched, generating a microporous structure with a pore size of 5–20 μm. Immediately rinse the etched copper foil three times with deionized water to remove residual etching solution. Immerse the copper foil in a chromate passivation solution (containing 5 g / L CrO3 and 1 g / L H2SO4) at room temperature for 10 seconds to form a passivation film. After removal, blow dry and then dry with hot air at 80°C for 5 minutes to obtain a microporous copper foil with no surface oxidation and uniform distribution of blind holes.

[0064] Example 4:

[0065] Oxidizing agent: hydrogen peroxide (H2O2, 30% concentration), dosage 30 g / L; Corrosion inhibitor: benzotriazole (BTA), dosage 10 g / L, 2-mercaptobenzimidazole (C7H6N2S), dosage 5 g / L; Complexing agent: citric acid (C6H8O7), dosage 10 g / L; tartaric acid (TA), dosage 5 g / L; Surfactant: betaine (C5H 11 NO2), dosage 0.2 g / L. Dissolve the above components sequentially in water, stirring until completely mixed. Adjust the pH of the solution to 2-3 with dilute sulfuric acid to obtain a homogeneous and transparent etching solution. Pour the prepared etching solution into the electrolytic cell, ensuring the liquid level completely covers the copper foil. Use a 6 μm thick electrolytic copper foil as the anode (10 cm × 10 cm), with a surface roughness ≤ 1.5 μm; use a titanium plate with uniformly distributed micro-bumps on its surface as the cathode (spacing: 3 mm). Connect a DC power supply and control the current density to 50 mA / cm². 2 The etching time was 10 seconds. During etching, the solution temperature was maintained at 25±2℃, and continuous circulation and stirring were performed to eliminate concentration polarization. After etching, uniformly distributed oxide sites formed on the copper foil surface. After immersion in dilute hydrochloric acid (5% concentration) for 5 seconds, the oxide sites were selectively etched, generating a microporous structure with a pore size of 5–20 μm. The etched copper foil was immediately rinsed three times with deionized water to remove residual etching solution. It was then immersed in a chromate passivation solution (containing 5 g / L CrO3 and 1 g / L H2SO4) at room temperature for 10 seconds to form a passivation film. After removal, it was blown dry and then dried with hot air at 80℃ for 5 minutes to obtain a microporous copper foil with no oxidation on the surface and a uniform distribution of blind holes.

[0066] As shown in the above embodiments, the present invention provides a method for preparing microporous copper foil, comprising the following steps: mixing an oxidant, a corrosion inhibitor, a complexing agent, a surfactant, and water, adjusting the pH value to obtain an etching solution; using an electrolytic copper foil as the anode and a cathode plate at a specific location as the cathode, performing electrochemical etching in the etching solution to form a copper foil; cleaning the etched copper foil and then placing it in an anti-oxidation solution for passivation treatment to obtain a microporous copper foil. The method provided by the present invention uses a copper foil as a corrosive anode, forming an electrolytic cell with a cathode plate at a specific location and the etching solution, and performs site oxidation on the surface of the copper foil using an oxidant, forming blind holes through acid etching at the sites; to ensure uniform corrosion of the copper foil and the formation of blind holes, a corrosion inhibitor, surfactant, and complexing agent are combined to reduce the corrosion rate of the copper foil; this method can effectively control the formation and pore size of the micropores in the copper foil. Experimental results show that this method produces copper foil with a uniformly distributed microporous structure of 5–20 μm with no surface oxidation.

[0067] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A method for preparing microporous copper foil, comprising the following steps: An oxidant, corrosion inhibitor, complexing agent, surfactant, and water are mixed, and the pH value is adjusted to obtain a corrosion solution. Electrochemical etching is performed in an etching solution using electrolytic copper foil as the anode and a cathode plate at a specific location as the cathode to form copper foil. The etched copper foil is cleaned and then passivated in an anti-oxidation solution to obtain microporous copper foil.

2. The preparation method according to claim 1, characterized in that, The oxidant is selected from one or more of hydrogen peroxide, potassium permanganate, and hypochlorous acid; The corrosion inhibitor is selected from benzotriazole and / or 2-mercaptobenzimidazole; The complexing agent is selected from one or more of citric acid, tartaric acid and succinic acid; The surfactant is selected from sodium dodecyl sulfate and / or betaine.

3. The preparation method according to claim 2, characterized in that, The concentration of the oxidant is 10–100 g / L; the concentration of the corrosion inhibitor is 1–20 g / L; The concentration of the complexing agent is 5–50 g / L; the concentration of the surfactant is 0.2–2 g / L.

4. The preparation method according to claim 2, characterized in that, Adjust the pH value to 2-3 using dilute sulfuric acid.

5. The preparation method according to claim 1, characterized in that, The corrosive solution consists of 50 g / L hydrogen peroxide (30% by mass), 10 g / L benzotriazole, 30 g / L citric acid, and 0.5 g / L sodium dodecyl sulfate. Alternatively, the corrosive solution may contain 10 g / L potassium permanganate, 6 g / L 2-mercaptobenzimidazole, 18 g / L citric acid, 10 g / L tartaric acid, and 0.5 g / L sodium dodecyl sulfate. Alternatively, the corrosive solution may comprise 50 g / L hydrogen peroxide, 10 g / L benzotriazole, 10 g / L citric acid, 5 g / L succinic acid, and 0.2 g / L betaine, all at a mass fraction of 30%. Alternatively, the corrosive solution may comprise 30 g / L hydrogen peroxide, 10 g / L benzotriazole, 5 g / L 2-mercaptobenzimidazole, 10 g / L citric acid, 5 g / L tartaric acid, and 0.2 g / L betaine, all at a mass fraction of 30%.

6. The preparation method according to claim 1, characterized in that, The cathode plate is a titanium plate with multiple micro-protrusions evenly distributed on its surface.

7. The preparation method according to claim 6, characterized in that, The distance between adjacent micro-bumps is 2 to 10 mm.

8. The preparation method according to claim 1, characterized in that, The etching process uses a current density of 20–50 mA / cm². 2 ; The etching time is 10 to 30 seconds.

9. The preparation method according to claim 1, characterized in that, The main component of the anti-oxidation solution is chromium passivation solution.

10. The preparation method according to claim 1, characterized in that, Acid etching is performed before cleaning; the acid etching is performed by soaking in dilute hydrochloric acid with a mass fraction of 3-6% for 4-6 seconds to form a microporous structure with a pore size of 5-20 μm.